The Impact of Artificial Intelligence Adoption on Job Satisfaction and Productivity of Healthcare Workers in Hospitals - Mochammad Isa Anshori; Ari Akbar; Djamaliyah; Aisyah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The integration of artificial intelligence in healthcare is transforming hospital operations, particularly in enhancing employee satisfaction and productivity. While AI offers opportunities to reduce administrative burden, foster teamwork, and improve patient care, it also introduces challenges related to technology adaptation and employee concerns about automation. This study aims to investigate how artificial intelligence adoption influences hospital staff’s job satisfaction and productivity, linking its application not only to efficiency but also to employee engagement and service outcomes. This research employs a qualitative methodology using a case study approach. Data were collected through semi-structured interviews, observation, surveys, and document analysis to capture healthcare workers’ perceptions of artificial intelligence in daily work and its influence on work-life balance. Findings reveal that artificial intelligence enhances job satisfaction by simplifying documentation, supporting skill development, improving decision-making, and creating opportunities for innovation. Productivity improvements include faster clinical decisions, better time management, effective human-technology collaboration, and higher-quality patient care. artificial intelligence adoption contributes significantly to operational success in hospitals by fostering innovation, supporting staff development, and balancing technological advancement with human needs, provided continuous training and transparent communication are ensured.